Indigenous Peoples Movement in Maintaining Living Spaces Perspective of Recognition Politics (Study on Indigenous Peoples in Lake Toba) - Cusdiawan; Mudiyati Rahmatunnisa (Universitas Medan Area, 2023)
This study aims to explore the process of indigenous peoples' movement in Lake Toba in maintaining their living space from the perspective of political recognition. The method used in this study is qualitative, because the strength of a qualitative study is when examining the process. This study argues that the politics of recognition is an important aspect in the struggle of indigenous peoples in Lake Toba in maintaining their living space in the midst of developments carried out by corporations and the State that threaten the existence of local communities. For the community, land is ancestral heritage that needs to be maintained and is a symbol of self-esteem for them. Development that destroys and threatens their land also threatens their cultural identity. They also demanded that the values ​​of their identity as indigenous peoples be recognized by the State. Recognition is also an effective value in mobilizing citizens to carry out social movements. The relationship between the indigenous peoples' movement and the state itself, on the one hand, the state seeks to accommodate people's demands, but on the other hand, society accepts repressive measures. In this context, the state is seen as a tool for the interests of investors or corporations, because the state has the authority to make regulations, including licensing matters. This study further confirms the importance of recognition politics in the civic politics discourse. As for social movements from indigenous peoples in the form of protests to direct dialogue with the government.